Pemanfaatan Data Global Precipitation Measurement (GPM) dan Standardized Precipitation Index (SPI) untuk Deteksi Kekeringan Meteorologis di Provinsi Papua Barat - Arif faisol; Budiyono Budiyono; Indarto Indarto; Elida Novita (Jurnal Agritechno, 2020)
Drought is a natural disaster in Indonesia. The National Disaster Management Agency (BNPB) reports that West Papua Province has a moderate to high threat of drought. This study aims to analyze the level of drought in West Papua Province using Global Precipitation Measurement (GPM) data and the Standardized Precipitation Index (SPI) method. The results showed that throughout 2019 there was no meteorological drought in West Papua, only a few areas in Kaimana were rather dry in the January-March 2019 SPI. In general, the GPM data and the SPI method have quite good accuracy in describing the level of meteorological drought in The Province of West Papua is compared with the analysis of rainfall data and drought level maps released by the Meteorology, Climatology and Geophysics Agency (BMKG), so that the GPM data and SPI method can be used to monitor the level of drought in West Papua Province especially in agricultural areas.